Mercury distribution and reactivity in waters of a subtropical coastal lagoon, Sepetiba Bay, SE Brazil - Lacerda,Luiz D. (2001)
A survey of the reactive and total Hg concentrations in surface waters and of the quantity of particulate organic carbon (POC) and dissolved organic carbon (DOC), were performed along a transect from the major rivers mouths and mangrove dominated areas to the open bay waters of Sepetiba Bay, SE Brazil. The objective of the survey was to evaluate changes in Hg reactivity during the transport along the estuarine gradient. Reactive Hg concentrations were lowest in open bay waters, (0.09 ± 0.06 ng L-1), followed by river influenced waters (0.19 ± 0.06 ng L-1), and mangrove (0.29 ± 0.02 ng L-1). Total Hg concentrations were lowest in open bay (0.38 ± 0.20 ng L-1), followed by mangrove waters (0.56 ± 0.01 ng L-1), and river influenced waters (0.99 ± 0.29 ng L-1). The percentages of reactive Hg relative to the total Hg concentrations were lowest in river influenced waters, (20.7%), followed by open bay waters (31.2%), and mangrove waters (53.2%). The percent of reactive Hg to the total Hg concentrations showed a significant negative correlation with the total Hg concentrations following a potential equation. No relationship between reactive Hg concentrations and POC, salinity or pH were found, however, reactive Hg correlates significantly with DOC, suggesting that organo-complexes, rather than chloro-complexes, are the major controllers of Hg reactivity, and eventually bioavailability in Sepetiba Bay.